Existence Uniqueness and Decay of the Global Weak Solutions for a Class of Parabolic Systems with Nonlinear Boundary Conditions (Journal of Partial Differential Equations, 2020)
In this paper, a class of parabolic systems with nonlinear boundary conditions is discussed. By introducing a complete metric space with decay of W^s_p-norm, we obiain the existence uniqueness of global weak solutions, our method is simpler than before. A decay estimate of the global weak solutions is obtained simultaneously.
Keywords: Nonlinear boundary conditions; global weak solutions; deeay